ANALISIS KECEPATAN KELUARAN ANGIN KONDENSOR AC TERHADAP JENIS–JENIS BLADE GENERATOR LISTRIK DENGAN KOMPUTASI FLUIDA DINAMIK: Analysis of AC Condensor Wind Output Speed to Types of Electric Blade Generator with Computational Fluid Dynamics - Wahid Wahyu Saputro; Golwa, Gian Villany (Jurnal Konversi Energi dan Manufaktur, 2024)
Electrical energy is widely used for household and industrial purposes, so the need for electrical energy will continue to increase every year. Therefore, it is necessary to develop an electrical energy generation system that comes from renewable energy such as wind. Currently, not much is known about the use of wasted wind from air conditioner (AC) condensers. The blow of wind can be used to produce electrical energy, so it is necessary to make wind-powered electric generator blades from the condenser output. The blade that will be designed is a three-blade model, so it is hoped that it can rotate the generator optimally. The purpose of this research is to design a three-blade type that can optimize the rotation of the electric motor/generator and get the maximum number of revolutions with a three-blade design because this design provides better stability and more efficiency. One way of making the design is to make simulation variations with computational fluid dynamics (CFD) in order to find out the right blade design to rotate the generator and find out the wind blowing from the air conditioner (AC) condenser that crosses the blade. In this study, three simulations were carried out to get maximum results, namely 390 rpm at 42 °C with a velocity of 10.7 m/s and a pressure of 34.4 Pa. To be able to determine the effectiveness of the AC condenser wind output speed with a three-blade design.